IMPLEMENTATION OF DOUBLE EXPONENTIAL SMOOTHING HOLT METHOD IN FORECASTING COMMERCIAL RICE SALWS IN PERUM BULOG SUB DIVRE MEDAN - Agustine, Venina; Indra, Zulfahmi; Nasution, Hamidah (UIN Sumatera Utara, 2022)
Logistics general company or Perum BULOG is a state-owned public company engaged in food logistics, especially rice. To carry out its functions, this agency is assisted by several regional divisions or subdivisions, one of which is the Medan Sub-Divisional Division having its address at Timbang Deli, Medan Amplas District, Medan City. Forecasting is a technique for estimating a value in the future by paying attention to historical data or current data. The purpose of this study is to analyze data based on historical data patterns and predict using the Double Exponential Smoothing Holt method by finding optimal parameters based on the smallest MAPE value. The results of this study obtained a graph of data patterns that experienced an upward trend so that it could be predicted using the Double Exponential Smoothing Holt method with optimal parameters , namely dan and based on the smallest MAPE value, which was 0,0418052 and also obtained the results of forecasting commercial rice sales at Perum BULOG Sub Divre Medan which will increase by 151,3 kg every month, namely in January 2022 by 865369 kg, in February 2022 by 865540,3 kg, in March 2022 by 865691,6 kg, in April 2022 by 865842,9 kg, in in May 2022 amounted to 865994,2 kg, and in June 2022 amounted to 866145,5 kg.